Men in love with artificial women - Uvanović, Željko (Primerjalna književnost, 2016)
This paper provides a new reading of E. T. A. Hoffmann's romantic novella "Der Sandmann" and of Ira Levin's postmodernist SF thriller novel The Stepford Wives in the context of their film adaptations. The phenomenon of Pygmalionism and agalmatophilia has been traced from the Greek antiquity up to now and has been used as a net of significant analogies with literary works. Additionally, the occurrence of male attraction to artificial, non-responding female surrogates has been interpreted in the context of the diagnoses of Asperger's syndrome and narcissism. New insights about Hoffmann's novella could be gained in multiple intertextual, intermedial comparative procedures whereas Levin's novel has been critically put into relationship with another literary work for the first time. The comparison has shown interesting similarities between the two literary works, alerted to the intensification of sexual alienation problems in the course of time up to now, and has warned of disagreeable consequences of certain uncanny tendencies if reality-based and digital agalmatophilia continues.
Keywords: film; književnost; literature; ljubezen; love; pigmalionizem; agalmatofilija; German-language literature; nemška književnost; American literature; ameriška književnost; filmske priredbe; Hoffmann, E. T. A.: Peščeni mož; Levin, Ira: Stepfordske ženske